(untitled) (Journal of actual problems of jurisprudence, 2020)
The problem of the ratio of legal categories to “civil law” and “civil process” is a debatable one in the civility procedural doctrine. For the purposes of this study, these legal categories are used as identical. The term “civil proceedings” is used in the current procedural legislation. In the light of the reform of the current procedural legislation, the definition of the concept, purpose and objectives of civil litigation is a relevant. The concept of civil procedure (process) in the doctrine of civil procedural law is debatable. The science of civil procedural law discusses the concepts of a broad and narrow understanding of the civil process. Proponents of narrow interpretation refer to the civil process only the work of the court to implement justice in civil cases. As well as the scientific article states theoretical and practical research of civil proceedings as specialization as a procedural form. General provisions having initial importance for such cognition by the science of civil procedure law are defined and characterized, their influence on specialization and its characteristic is also recognized. According to the authors, this approach reflects the development of branch domestic legislation and law, legal practice and legal doctrine, with a special role – procedural. It allows to correctly establish and correctly explain, holistically and systematically understand the legal form of the procedural form and its action in accordance with the subject of the judicial examination, when the results achieved are verified, confirmed or denied its perfection. Key words: civil procedure, civil proceedings, arbitration process, procedural form, the science of civil procedure law, specialization as a research area.